Empreendedor social: entre a educação formal, informal e não formal - Itelvino, Lucimar da silva (2015)
This study aimed mainly to investigate the assessment of the process of developing of the social entrepreneur´s formation. For the analysis of this process, it was necessary to recognize the spaces and contexts of entrepreneurs´ formation, their social motivations and their ways of social leadership, in other words, the present elements in the professional and social individual development which are generators of social-environmental transformations. The research took qualitative aspect and included the analysis of 59 social entrepreneurs´ life stories, published during the period 2005-2013 by the newspaper Folha de S. Paulo, responsible for the Social Entrepreneur Award contest in Brazil, in close partnership with the Schwab Foundation. The methodological organization was through two separate analyzes, both managed by the ATLAS software. First they were analyzed 10 contest winners, and on the second step the other finalists of the contest in the same period. The results obtained from conclusions provided (a) the combination of methodologies that integrate and systematize theoretical knowledge; (b) the possibilities of entrepreneurship in different learning areas of "formal," "informal" and "nonformal"; and finally, (c) the propose a model for the Social Entrepreneur´s formation process.